Avtorskopravno varstvo improvizirane glasbe - Prete, Valentina (Pravni letopis, 2018)
The article presents an in-depth overview of the copyright status of improvised music and highlights the chosen key features in which the copyright regime on improvised music slightly differs from that of more conventional and non-improvised music pieces. The copyright and related rights of a live performance, as well as the problem of their collective management, are defined and described through various levels of improvisation. The final part of the article presents the results of the empirical research recently conducted among musiciansimprovisers, and critically evaluates certain discrepancies between theoretical starting points and the management of copyright in practice.
Keywords: avtorske pravice; avtorsko pravo; glasba; improvizacija